2014
DOI: 10.1080/10942912.2013.877025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blueberry (Vaccinium corymbosum) Juice on Lipid Oxidation During Spray Drying of Microencapsulated Menhaden Oil

Abstract: This study investigated the effect of blueberry juice on menhaden oil lipid oxidation during microencapsulation. Oil in water emulsions containing menhaden oil with 0, 5, or 10% blueberry juice were spray dried to produce control-M, 5% BJ-M, and 10% BJ-M microencapsulated powders, respectively. All microencapsulated powders had similar encapsulation efficiencies with low surface oil content. Peroxide value (meq/kg of oil) was 4.50, 4.31, and 3.38 for control-M, 5% BJ-M and 10% BJ-M, respectively. Ten percent B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Gupta and Jadhav [13] stressed that it is important to protect PUFA in edible oil against lipid oxidation in order to boost its shelf life, which can be accomplished by applying the efficient technique of microencapsulation. Due to the many advantages of the spray drying method, it is commonly used for microencapsulation in the food sector as well documented in the literature: Terminalia arjuna extracts [14] , pequi extracts [15] , fish oil, [16] flaxseed oil, [17] menhaden oil, [18] and chili seed oil. [19] A crucial objective to ensure the usefulness of spray-dried products for food application is to evaluate its stability and functionality during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta and Jadhav [13] stressed that it is important to protect PUFA in edible oil against lipid oxidation in order to boost its shelf life, which can be accomplished by applying the efficient technique of microencapsulation. Due to the many advantages of the spray drying method, it is commonly used for microencapsulation in the food sector as well documented in the literature: Terminalia arjuna extracts [14] , pequi extracts [15] , fish oil, [16] flaxseed oil, [17] menhaden oil, [18] and chili seed oil. [19] A crucial objective to ensure the usefulness of spray-dried products for food application is to evaluate its stability and functionality during storage.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing of MCL extract was affected the surface content to be increased whereas the encapsulation efficiency was decreased as shown in Table I. These results happened due to the increasing of core-towall as suggested in Mohideen et al [29] investigation on encapsulating of blueberry juice using spray drying.…”
Section: A Physical and Encapsulation Properties Of MCLmentioning
confidence: 79%
“…To the best of our knowledge, there are no previous data on the use of blueberry phenolic extracts encapsulated in microemulsions and liposomes on the prolongation of the oxidative stability of edible oils. Mohideen et al [2015] studied the effects of blueberry juices on lipid oxidation during spray drying of menhaden oil and they found that 10% of blueberry juices Table 1).…”
Section: The Effect Of Native and Encapsulated Blueberry Phenolic Extmentioning
confidence: 99%